Integrin-dependent phosphorylation and activation of the protein tyrosine kinase pp125FAK in platelets (The Rockefeller University Press, 1992)
We have investigated mechanisms involved in integrin-mediated signal transduction in platelets by examining integrin-dependent phosphorylation and activation of a newly identified protein tyrosine kinase, pp125FAK (FAK, focal adhesion kinase). This kinase was previously shown to be localized in focal adhesions in fibroblasts, and to be phosphorylated on tyrosine in normal and Src-transformed fibroblasts. We show that thrombin and collagen activation of platelets causes an induction of tyrosine phosphorylation of pp125FAK and that pp125FAK molecules isolated from activated platelets display enhanced levels of phosphorylation in immune-complex kinase assays. pp125FAK was not phosphorylated on tyrosine after thrombin or collagen treatment of Glanzmann's thrombasthenic platelets deficient in the fibrinogen receptor GPIIb-IIIa, or of platelets pretreated with an inhibitory monoclonal antibody to GP IIb-IIIa. Fibrinogen binding to GP IIb-IIIa was not sufficient to induce pp125FAK phosphorylation because pp125FAK was not phosphorylated on tyrosine in thrombin-treated platelets that were not allowed to aggregate. These results indicate that tyrosine phosphorylation of pp125FAK is dependent on platelet aggregation mediated by fibrinogen binding to the integrin receptor GP IIb-IIIa. The induction of tyrosine phosphorylation of pp125FAK was inhibited in thrombin- and collagen-treated platelets preincubated with cytochalasin D, which prevents actin polymerization following activation. Under all of these conditions, there was a strong correlation between the induction of tyrosine phosphorylation of pp125FAK in vivo and stimulation of the phosphorylation of pp125FAK in vitro in immune- complex kinase assays. This study provides the first genetic evidence that tyrosine phosphorylation of pp125FAK is dependent on integrin- mediated events, and demonstrates that there is a strong correlation between tyrosine phosphorylation of pp125FAK in platelets, and the activation of pp125FAK-associated phosphorylating activity in vitro.